Operative subdivisions of law enforcement bodies of Ukraine as the subjects of counteraction to the crimes in the international student exchange - Черняк, А.М (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
The article deals with the defnition of the list and functions of the operative subdivisions authorized to counteraction to the criminal activity in the international student exchange. The legal problems in the activities of subdivisions, whose competence is counteraction to the criminal ofense, are determined. The ways of solving these problems are given.It notes that the main crimes in the international student exchange is illegal migration in the form of trafcking the persons across the state border of Ukraine. These crimes are mostly combined with others, which can diferentiate into two categories: those that are necessary for the smooth committing illegal migration (obtaining undue advantage by an ofcial forgery of documents, seals, stamps, use of forged documents, etc.) and those for the commission of which the illegal migration doing (espionage, sabotage, terrorism, crime in economic activity, human trafcking, etc.).Among the operative units of law enforcement agencies counteracting of crimes is investigated operational units of the National Police, the Security Service of Ukraine and the State Border Service (under the jurisdiction specifed by the Criminal Code of Ukraine), authorized to prevent the occurrence of specifed criminal ofenses, detect and take part in their pre-trial investigation in the form of execution the prosecutor’s orders in the investigation (search) actions including undercover ones. For some cases, these functions may be execute by the operational units the other law enforcement bodies

Визначено перелік та функції оперативних підрозділів, уповноважених протидіяти злочинній діяльності у сфері міжнародного студентського обміну. Окреслено юридичні проблеми, що мають місце у діяльності підрозділів, компетенцію яких становить протидія вказаним кримінальним правопорушенням. Визначено шляхи вирішення цих проблем
ОПЕРАТИВНІ ПІДРОЗДІЛИ ПРАВООХОРОННИХ ОРГАНІВ УКРАЇНИ ЯК СУБ’ЄКТИ ПРОТИДІЇ ЗЛОЧИНАМ У СФЕРІ МІЖНАРОДНОГО СТУДЕНТСЬКОГО ОБМІНУ
Keywords: crimes in international student exchange; operational units; operational-investigative activity; criminal process; злочини у сфері міжнародного студентського обміну; оперативні підрозділи; оперативно-розшукова діяльність; кримінальний процес